2022
DOI: 10.1101/2022.02.04.479203
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dopamine transporter and synaptic vesicle sorting defects initiate auxilin-linked Parkinson’s disease

Abstract: Auxilin participates in the uncoating of clathrin-coated vesicles (CCVs), thereby facilitating synaptic vesicle (SV) regeneration at presynaptic sites. Auxilin (DNAJC6/PARK19) loss-of-function mutations cause early-onset Parkinson's disease (PD). Here, we utilized auxilin-knockout (KO) mice to elucidate the mechanisms through which auxilin deficiency and clathrin-uncoating deficits lead to PD. We demonstrate that auxilin KO mice display the cardinal features of PD, including progressive motor deficits, α-synuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 69 publications
(111 reference statements)
0
14
1
Order By: Relevance
“…We did not observe any obvious motor phenotypes, including hindlimb clasping, in the Vps13c −/− mice up to 2 yr of age, nor did we observe any effect on lifespan. We assessed for motor phenotypes that had shown differences in other PD mouse models ( Cao et al, 2017 ; Vidyadhara et al, 2022 ). Balance beam testing at 6 mo of age showed no difference between Vps13c −/− mice and heterozygous controls ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We did not observe any obvious motor phenotypes, including hindlimb clasping, in the Vps13c −/− mice up to 2 yr of age, nor did we observe any effect on lifespan. We assessed for motor phenotypes that had shown differences in other PD mouse models ( Cao et al, 2017 ; Vidyadhara et al, 2022 ). Balance beam testing at 6 mo of age showed no difference between Vps13c −/− mice and heterozygous controls ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They have been previously reported to be potential axonal branching points 55 and are presently viewed to be highly relevant in neural injury and neurodegeneration. 56 , 57 , 58 We found that only varicosities, but not axonal shafts or boutons exhibited a robust NH 4 Cl response ( Figures 4 B and 4C). No significant difference was observed for the MES responses ( Figure 4 C).…”
Section: Resultsmentioning
confidence: 77%
“…Recent studies have suggested molecules important for clathrin coat removal, such as synaptojanin1 (Synj1) or auxilin1, play a crucial role in DAT expression and/or trafficking. 40 , 57 , 58 We therefore decided to investigate if Synj1 deficiency influences cocaine-regulated DAT trafficking using this new reporter. Of interest, in neurons carrying a heterozygous mutation of Synj1 ( Synj1 +/− ), a larger deflection was observed ( Figures 6 A and 6B), which could suggest increased endocytosis of DAT or delivery of DAT to more acidic intracellular structures.…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 14 , 15 Aux-KOs can be used to build a faithful model of DNAJC6 -linked PD in mice and Drosophila, recapitulating the cardinal features of nigrostriatal neuronal loss, alpha-synuclein pathology, and motor deficits. 16 , 17 , 18 As auxilin is broadly expressed in the brain and its endocytic function is universal to all synapses in the central nervous system, loss-of-auxilin is likely to impact the functions of brain regions beyond documented regions such as the hippocampus, dorsal striatum, and substantia nigra. 18 , 19 Because cognitive deficits are a common symptom of PD patients, including PARK19 patients, we utilized Aux-KO to explore the basis of these symptoms.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 , 18 As auxilin is broadly expressed in the brain and its endocytic function is universal to all synapses in the central nervous system, loss-of-auxilin is likely to impact the functions of brain regions beyond documented regions such as the hippocampus, dorsal striatum, and substantia nigra. 18 , 19 Because cognitive deficits are a common symptom of PD patients, including PARK19 patients, we utilized Aux-KO to explore the basis of these symptoms. We chose to investigate the primary visual cortex due to the ease of assays to interrogate cortical functions and as a subset of PD patients suffers from visual disturbances, such as visual hallucinations and pattern recognition deficits, attributed partially to malfunctions of the primary visual cortex in humans.…”
Section: Introductionmentioning
confidence: 99%